PERTUMBUHAN SYI’AH DAN RELASINYA DENGAN NON SYI’AH DI KOTA MEDAN SUMATRA UTARA - Wakhid Sugiyarto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
This paper is the result of a research conducted in 2016 that was back-grounded by several persecutions, intimidations, and violence towards Shi’i-related communities. Those persecutions, intimidations, and violence was based on many negative accusations that have been long addressed to them across the globe. The research is conducted within qualitative approach. The data collection includes techniques of Focused Group Discussion (FGD), observation, interview, and documentary study. The objective of this study is to describe the growth of the Shi’i community, the testimony that led them to convert to Shi’ism, as well as to describe their relations with other Muslim community. The research discovers the new real situation, that Shi’ism has developed quickly among educated people and students in Medan. They have formed and sponsored the foundation of many Shi’i religious circles (Majelis Taklim) in many regions (kabupaten kota) within the Province of North Sumatera, several circles in the Provinces of West Sumatera and Aceh. In addition, the relations of Shi’i community with other Muslim societies develop well. This can be seen from the establishment of the Islamic Foundation of Abu Thalib in Medan that was attended by the Rector of UIN of North Sumatera, the Director of Post-Graduate Studies of UIN of North Sumatera, religious figures of any religious organisations, and most of the members of the society.